PENGARUH PENERAPAN TEKNOLOGI PERTANIAN ORGANIK TERHADAP EFISIENSI PENGGUNAAN INPUT PRODUKSI DAN EFISIENSI USAHATANI PADI ORGANIK: (Kasus Pada Petani di Kecamatan Rawamerta, Kabupaten Karawang, Provinsi Jawa Barat) - Sobana, Neng Tita Srijuwita (Fakultas Pertanian Universitas Winaya Mukti, 2025)
NENG TITA SRIJUWITA SARI, 2024. Analysis of Factors Affecting the Application of Organic Rice Farming Technology in Cianjur Regency. (Case of Farmer in Rawamerta District, Karawang Regency). Under the guidance of Euis Dasipah and Nataliningsih. This study aims to determine the effect of the application of organic rice technology on the efficiency of using production inputs and the efficiency of farming. This study used a survey method of farmers who applied organic rice. The respondent determination technique used was a census obtained by 60 respondent farmers. The form of research is verifiative and the analytical techniques used are Cobb-Douglas model regression and Variance Analysis. The results of the study were obtained Demonstration of the application of organic rice farming technology in Rawamerta District, Karawang Regency .showed very good achievements with an average land area. 0.57 ha and profitable indicated agricultural efficiency R/C = 2.56. The application of technology affects the technical efficiency of the use of production inputs in organic rice farming which can be seen from the use of production inputs: land, seeds, organic fertilizers, POC, organic pesticides and work outpouring has a value of input elasticity coefficient values between zero and one. But none of the uses of production inputs have been economically efficient. The level of application of technology affects the efficiency of organic rice farming. It is proven that there are differences in agricultural efficiency according to the class of technology application. Keywords: Rice, Organic, Efficiency,